Impact of the Environmental Quality Index (IKLH), Inflation, and Unemployment Rate on Economic Growth in Indonesia - Claudia, Emilia Ruth; Fitrawaty, Fitrawaty; Nugrahadi, Eko Wahyu (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze the impact of the Environmental Quality Index, Inflation, and Unemployment Rate on Economic Growth in Indonesia. This study uses secondary panel data from 34 provinces in Indonesia for the period 2018–2022. This analysis uses panel data regression with the Fixed Effect Model (FEM) approach to examine the relationship between variables. The dependent variable is economic growth, measured by Gross Regional Domestic Product, while the independent variables include the Environmental Quality Index, inflation, and unemployment rate. The findings reveal that the Environmental Quality Index has no effect on economic growth in Indonesia. On the contrary, inflation has a negative and significant impact on economic growth, highlighting the importance of price stability in supporting household purchasing power and economic activity. Likewise, the unemployment rate has a negative and significant effect on economic growth in Indonesia. This underscores the important role of job creation to support economic progress. This study provides theoretical and practical contributions, especially in environmental management, economic stability, and unemployment reduction as a joint effort to encourage sustainable economic growth in Indonesia. These findings are also relevant for policymakers in designing economic development strategies that balance environmental preservation, price stability, and social welfare to achieve inclusive and sustainable development.